Research Progress on Surface Modification of Bipolar Plates for PEMFC - LI Cong, JIN Rongzhen, REN Yanjie, TANG Chunmei, HONG Yue (Cailiao Baohu)
The bipolar plates are one of the core components of the proton exchange membrane fuel cell (PEMFC),and its performance directly affects the output power and service life of the battery stack.Bipolar plates not only connect individual cells into stacks and provide support,but also provide gas flow paths and isolate the anodes and cathodes, playing a key role in the operating performance and lifetime of fuel cells.Due to the harsh service environment of PEMFC, including high temperature, high humidity and acidic environment, the bipolar plates need to have excellent electrical conductivity and corrosion resistance to ensure the efficient and stable operation of the fuel cell.In this paper, the development status and application progress of PEMFC bipolar plates were briefly described.The research and development of surface modification schemes for electrical conductivity and corrosion resistance were emphatically expounded.Moreover, the surface modification schemes of stainless steel, titanium, titanium alloy, aluminum alloy and other metal bipolar plate’ substrates were systematically introduced.The performance characteristics, development trends and existing problems of different metal bipolar plates and their surface modification schemes were compared.Finally, the common problems and development and application prospects of the surface modification of PEMFC metal bipolar plates were discussed.